Two centuries of ornithological exploration of the Rio Doce basin, southeastern Brazil. Part I—A history of the landscape, its explorers, and their collections - Lopes, Leonardo Esteves; Baptista, Michelle Noronha Da Matta; Reis, Jéssica Naiara; Pacheco, José Fernando; Heming, Neander Marcel (Zootaxa, 2023)
The Rio Doce Hydrographic Basin (RDB) was once covered by magnificent tropical forest, which remained untouched by Europeans for three centuries after the arrival of the Portuguese colonists in the Brazilian coast in 1500. Nevertheless, a dramatic change in land use occurred throughout the entire RDB after the turn of the 19th century. Currently, the RDB is one of the most degraded regions in southeastern Brazil and, recently, it was the scenario of the worst environmental disaster in Brazilian history. In this series of papers, we aim to construct a baseline biodiversity assessment that documents the changes in bird communities within the RDB throughout the last two centuries. In this first part, we present the history of the RDB landscape, its explorers, and their collections based on an extensive literature review and museum data. Early biological surveys in the RDB only started at the beginning of the 19th century and were conducted mostly by German and French naturalists. During the first eight decades of ornithological exploration, foreign field naturalists conducted expeditions to the RDB and collected hundreds of bird specimens. Unfortunately, labelling and curatorial procedures were often poor and despite the prodigious efforts of those naturalists, results obtained were often meagre. The second phase of exploration occurred from the 1900s to the 1960s and was dominated by expeditions conducted by Brazilian natural history museums. During this phase, labelling and curatorial procedures improved considerably and the material collected significantly advanced our knowledge about the RDB avifauna The third phase occurred from the 1970s to the first decade of the 21st century, when collection of specimens decreased sharply and the research activity slowly shifted from museums to universities, with a focus on ecology and natural history. We are now in a fourth, more pluralistic phase, in which research continues to be done by universities, Brazilian natural history museums have resumed their collection activity, and birdwatching has emerged as a popular activity in Brazil, producing a tremendous amount of data in a short period of time.